Strategi Store Environment dan Time Pressure pada Pembelian Impulsif melalui Emotional State - Purwa, Enrique Made Reidia Gana; Yasa, Ni Nyoman Kerti (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2014)
The objective of the study was to analyze and explain the influence of store environment and time pressure toward impulsive purchases mediated by emotional state. The population of this study was the visitors Tiara Dewata Super Market. The sampling method used was purposive sampling, with 130 respondents. The data were analyzed by Structural Equation Model (SEM) and the Sobel test. The results of the study showed that the store environment and time pressure gave significant positive influence toward emotional state and impulsive purchases; emotional state was positive had significant influence on impulsive purchases; emotional state was significant to mediate the influence of store environment and time pressure toward impulse purchases. Thus with this study, it is expected for the management of Tiara Dewata Super Market to increase the visits and purchases by optimalizing the store environment.